Investigation of Ethiopian Cotton Fiber Stickiness. Part 1 – Northern Part. Issue 15 (23rd November 2022) - Atalie, Desalegn; Ashagre, Gashaw; Ferede, Eyasu; Getnet, Frezer; Nibret, Abiyou
ABSTRACT: Cotton is the most important natural textile fiber in the world used to produce apparel, home furnishings and industrial products. However, in the last decades cotton stickiness has become a very serious problem caused by excess sugars on the lint, either from the plant itself or from insects and it is a challenge for cotton growers, ginners, and spinners. It affects the processing efficiency as well as the quality of the product. Ethiopian textile industries are facing this problem every season and not solved it yet. In this article, the Ethiopian northern region cotton stickiness properties have been characterized and their spinning risk probability identified. The stickiness was measured for hand and roller ginned cotton fiber using sticky cotton thermo-detector (SCT), high-speed stickiness detector (CONTEST-S), high volume instrument method (CONTEST-F) and colorimetric method according to ES ISO 12027:2013 and UNI EN 14278–3 standard methods. The statistical analysis of test results showed that the studied locations' cotton fiber stickiness properties significantly change in SCT, CONTES-S and CONTEST-F methods at P -values of 0.0423, 0.003 and 0.008, respectively. The cotton stickiness has slightly reduced after the roller ginning process compared to hand ginning. Metema and Humera's cotton fiber have a better stickiness property than other northern areas. Generally, nine northern parts of Ethiopian cotton fiber stickiness resulted in a 'No Risk' class 'Low Risk' spinning risk probability grade.